Hydraulic evolution of high-density turbidity currents from the Brushy Canyon Formation, Eddy County, New Mexico inferred by comparison to settling and sorting experiments - Motanated K. (2017)
© 2016 Elsevier B.V. Hydraulic transformations in turbidity currents are commonly driven by or reflected in changes in suspended sediment concentrations, but changes preceding transformations can be difficult to diagnose because they do not produce qualitative changes in resultant deposits. This study integrates particle settling experiments and in situ detection of hydraulically contrasting particles in turbidites in order to infer changes in suspended sediment concentration during deposition of massive (Bouma T a ) sandstone divisions. Because grains of contrasting density are differentially sorted during hindered settling from dense suspensions, relative grading patterns can be used to estimate suspended sediment concentrations and interpret hydraulic evolution of the depositing turbidity currents.Differential settling of dense particles (aluminum ballotini) through suspensions of hydraulically coarser light particles (silica ballotini) with volumetric concentration, C v , were studied in a thin vessel by using particle-image-velocimetry. At high C v , aluminum particles were less retarded than co-sedimenting silica particles, and effectively settled as hydraulically coarser grains. This was because particles were entrained into clusters dominated by the settling behavior of the silica particles. Terminal settling velocities of both particles converged at C v ≥ 25%, and particle sorting was diminished.The results of settling experiments were applied to understand settling of analogous feldspar and zircon grains in natural turbidity flows. Distributions of light and heavy mineral grains in massive sandstones, Bouma T a divisions, of turbidites from the Middle Permian Brushy Canyon Formation were observed in situ by X-ray fluorescence microscopy (μXRF). Hydraulic sorting of these grains resulted in characteristic patterns of zirconium abundance that decreased from base to top within T a divisions. These profiles resulted from upward fining of zircon grains with respect to co-occurring feldspar grains. Although calculated settling velocity distributions for zircon grains in structureless sandstones were slower than those for feldspar grains at infinite dilution, calculated settling velocity distributions for zircon and feldspar grains in overlying black siltstone layers were identical. This evidence suggests that these sandstone divisions were deposited from hyperconcentrated suspensions where particle segregation was diminished and hydraulically fine grains were entrained with hydraulically coarse particles. Hydraulic fining of zircon grains during deposition implies that the suspended sediment concentration at the bases of turbidity currents increased even as the overall current evolved toward lower density as reflected by cessation of T a deposition and by hydraulic equivalence of zircon and feldspar grains in overlying low-density turbiditic siltstones. This evolution likely resulted from volumetric collapse of the turbidity currents.